Implementation of Environmental Cleansing Program in Building the Character of Environment Care in the Area of Public Elementary School 36, Sorong, Indonesia - Suboto, Muhammad (LENTERNAL: Learning and Teaching Journal, 2025)
This study aims to describe the implementation of an environmental cleanliness program as an effort to develop environmental awareness character among students at State Elementary School 36, Sorong City, and to examine the program’s effectiveness in fostering such character. The research employed a qualitative descriptive method, which was chosen to provide a detailed description of the implementation of the environmental cleanliness program at the school. Data were collected through observation, interviews, and documentation.The results indicate that the environmental cleanliness program has been implemented through various activities, including the maintenance of classrooms and school buildings, adequate lighting and air ventilation in classrooms, the provision of proper sanitation facilities, management of the school canteen, efforts to eradicate mosquito larvae, and the establishment of smoke-free zones. In addition, the school actively promotes cleanliness and sanitation. The program is supported by adequate facilities and infrastructure, enabling the creation of a clean, healthy, and conducive school environment for fostering students’ environmental awareness character. Thus, the environmental cleanliness program at State Elementary School 36, Sorong, has proven effective in shaping students’ environmental care character through a structured and sustainable approach.